Enhancing Lecturer Performance through Strategic Leadership and Work Motivation - Rifaatussalwa Hayati; Johar Permana; Djam’an Satori; Nur Aedi; S Supiani (FKIP UNIVERSITAS PAKUAN, 2025)
This research aims to analyze the influence of strategic leadership and work motivation on the performance of lecturers at private universities in Southeast Sulawesi. The research approach uses quantitative methods with descriptive and analytical designs. Data was collected through a survey of 1,067 lecturers and university leaders, then analyzed using statistical methods to identify the relationship between the variables studied. The data analysis technique was carried out using the Structural Equation Modeling (SEM) method assisted by AMOS software. This research uses a sampling technique based on the Slovin formula. The main instrument of this research is a structured questionnaire designed to measure research variables using the semantic differential scale. The research results show that strategic leadership has a significant influence on lecturer performance, both directly and through increasing work motivation. Effective strategic leadership is able to create a supportive work environment, increase work morale, and encourage lecturers to behave innovatively. Work motivation was found as a mediating variable that strengthens the relationship between strategic leadership and lecturer performance. This research provides a theoretical contribution to the development of literature related to strategies for improving lecturer performance in the higher education context, by highlighting the importance of the role of strategic leadership in encouraging lecturer performance. From a practical perspective, these findings offer strategic recommendations for university administrators to integrate strategic leadership and work motivation development programs as part of a strategy to improve lecturer performance.